Human Infestation with Dermanyssus gallinae (Acari: Dermanyssidae) in a Family Referred with Pruritus and Skin Lesions. - Mohammad Abdigoudarzi; Mahmoud S Mirafzali; Hamid Belgheiszadeh (Journal of Arthropod-Borne Diseases, 2014)
The poultry red mite, Dermanyssus gallinae is one of the most economically important ectoparasites in hens and some species of mammals worldwide. Cases of human infestation have been reported worldwide. In this study we report infestation in three members of a family referred with pruritus and allergic dermatitis rash. They have collected very small animals and carried them to the laboratory which later was confirmed as D. gallinae. They claimed that they had been bitten with this ectoparasite. This is the first case report of human infestation owing to D. gallinae from Iran.